Characterization of Cleaved Plasma Protein S with a Monoclonal Antibody-based Assay - Morbœuf, Olivier; Borgel, Delphine; Gaussem, Pascale; Vincenot, Anne; Pittet, Jean-Louis; Aiach, Martine; Gandrille, Sophie (Thrombosis and Haemostasis, 2000)
A monoclonal antibody (mAb 5A5G2) recognized cleaved plasma protein S (PS) but not uncleaved PS. Interestingly, mAb 5A5G2 did not recognize thrombin-cleaved recombinant PS. Microsequencing of cleaved plasma PS showed a Q-S-T-N amino-terminal sequence, inferring cleavage after the Arg 60 residue. The mAb epitope was located within the sequence encompassing residues 61 to 73, i. e. the carboxyterminal part of the thrombin-sensitive region (TSR). We used this mAb to develop an ELISA assay to quantify in vivo cleaved PS. In plasma from 10 normal subjects, about 10% of PS was cleaved (7.1% to 15.4%), with a more than 2-fold increase in the corresponding sera. We found increased levels of cleaved PS in 8 patients with disseminated intravascular coagulation (DIC) and decreased levels in 22 patients on long-term oral anticoagulant therapy, whereas cleaved PS levels were similar in 8 hemophiliacs and the 10 normal subjects. Cleaved PS levels did not correlate with prothrombin fragment 1+2 levels released after cleavage by FXa in any of the groups, suggesting that circulating FXa is not the main factor involved in the production of cleaved PS in vivo.
Keywords: Cleaved plasma protein S; thrombin-sensitive region; monoclonal antibody; epitope mapping